INFLUÊNCIA DAS ETIQUETAS ELETRÔNICAS DE RFID NA CAPACIDADE DE REPELÊNCIA DE Melipona quadrifasciata (Apidae: Meliponini) AO IMIDACLOPRIDO - Castor, Rebeca Emanuelle da Silva (Universidade Federal de São Carlos, 2022)
Due to the importance of Brazilian stingless bees for pollination of native flora and the growing concern about the decline in pollinator populations triggered by environmental changes and the presence of pesticides, the number of studies involving these insects has increased. Therefore, to support conservation, the use of technologies such as Radio Frequency Identification tags (RFID) has been using as tools for environmental monitoring. For the purpose of evaluate the influence of electronic tags on bee behavior, the present study aimed to analyze behavioral parameters of locomotion and food resource choice between feeders with and without the neonicotinoid insecticide imidacloprid. To obtain the behavioral data, worker bees of M. quadrifasciata were individually placed in filming arenas for 10 minutes with availability of food contaminated with high and low concentration of the insecticide imidacloprid, 10 ppm and 10 ppb respectively, in addition to pure food and solvent control (Ntotal = 251 bees). It was observed that M. quadrifasciata bees do not have the ability to identify and avoid contaminated food, and the presence of the electronic tag did not change the frequency of visits between contaminated and pure food. The presence of food containing imidacloprid in the shooting situations reduced the movement time of the bees but did not interfere with other locomotion parameters. However, the electronic RFID tags interfered with the locomotion of the bees, so that it reduced the average speed, turning frequency, number of visits to the exit area, distance traveled, and movement time of the individuals. Therefore, under laboratory conditions the RFID tag influenced bee locomotion, but this technology has proven useful in behavioral research, and further studies are needed to understand if the behavioral effects observed in this work occur in field and colony situations
Influence of electronic RFID tags on the repellency of Melipona quadrifasciata (Apidae: Meliponini) to imidacloprid
Keywords: Abelhas nativas; Agrotóxicos; Comportamento; Conservação; Tecnologia; Native bees; Pesticides; Behavior; Conservation; Technology; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA